ANALISIS KUALITAS AIR SUNGAI DI KELURAHAN PAJALESANG KOTA PALOPO - Putu Darmawan; Sukarti; Nururrahmah Hammado; Nurmalasari (Cokroaminoto Journal of Chemical Science, 2023)
The river water which is passes through Pajalesang, Palopo City, through settlements and several industrial developments. Increasing population and development activities along river basins can lead to increased discharge of waste into water bodies. The river which is used as a place for waste disposal from the activities of the surrounding community can cause a decrease in water quality so that it does not meet the required quality standards for the use of clean water. This research aims to determine the quality of river water in Pajalesang, Palopo City. The research method was used several stages, namely sample preparation, data analysis using physical parameters (odor, taste and color, turbidity, total dissolved solids (TDS)), and data analysis using chemical parameters, namely pH, temperature, and iron (Fe) content. The results showed on the physical parameters of river water in Pajalesang, Palopo City, that it is odorless and when drunk it is tasteless and colorless, the resulting turbidity is 7.91 NTU, the total dissolved solids (TDS) are 70 mg/L and the temperature is 26.8ºC. It means that based on the physical parameters, the results exceeded the threshold standard requirements for clean water quality standards set by Minister of Health Regulation No. 32/2017. The chemical parameters in river water in Pajalesang, Palopo City showed that a pH value of 7.9 and a metal content of iron (Fe) of 0.1mg/L. The results also exceeded the threshold requirements for clean water quality standards based on chemical parameters.